Correlation between Refractive Errors, Axial Length, Corneal Curvatures and AL/CR ratio among first year undergraduate student in UiTM Puncak Alam, Selangor / Amalina Mohd Halil - Mohd Halil, Amalina (2016)
Purpose: This study was designed to study the correlation between refractive error, axial length, corneal curvature, AL/CR ratio and lens power among first year undergraduate students in UiTM Puncak Alam, Selangor. Methods: In this cross sectional study, 203 of first year undergraduate students in UiTM Puncak Alam, Selangor of mean age 20.78±0.93 years old volunteed themselves to participate as subjects. They underwent 3 procedures which were subjective refraction without cycloplegia by using Logmar chart, corneal radius (CR) of curvature by using NIDEK Corneal Topography and axial length (AL) by using TOMEY Biometer AL-100. The subjects were characterized according to these 3 variables to establish correlation between them. After determining the value of CR and AL, the ratio were calculated by dividing axial length with corneal radius to use in the analysis. Individuals with a history of ocular trauma, ocular surgery and take medication for systemic or ocular disease were excluded. Result: Out of 400 targeted subjects, 200 were included in the analysis. 71.5% of the subject were myopia (<-0.50D), 22.5% were emmetropia (>-0.50D - < +0.50 D) and 6% were hyperopia (<+0.50D). The correlation coefficient between spherical equivalent SE and CR, and AL/CR ratio were 0.187, and 0.829, respectively. The correlation between AL and CR was 0.253. The correlation between lens power and AL/CR ratio was 0.185. The r2 value of 0.687 suggests that 68.7% of the variance in refractive error can be accounted for the variation in AL/CR ratio. Mean AL/CR ratio was 3.12±0.18. Conclusion: The correlation between SE and AL/CR ratio was significantly stronger as compared to with AL and CR alone.